2017
DOI: 10.1177/0021998317731822
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural properties and mechanical behavior of magnesium/hydroxyapatite biocomposite under static and high cycle fatigue loading

Abstract: In this study, magnesium/hydroxyapatite biocomposites having 2.5 and 5 wt% of hydroxyapatite have been fabricated using stir casting followed by hot extrusion method. Both microstructural and mechanical behaviors of these composites have been studied, which contain particle distribution, grain size, microhardness, tension, and compression tests. Then, high cycle fatigue tests were performed using a rotating-bending testing machine (under stress ratio of R = −1). The results indicate an acceptable particle dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…It is calculated that the final strain is 0.21 with a slight reduction of 3%. Other studies have indicated similar results for compressive properties in terms of reduction and increase [52,53].…”
Section: Tensile and Compressive Propertiessupporting
confidence: 73%
See 1 more Smart Citation
“…It is calculated that the final strain is 0.21 with a slight reduction of 3%. Other studies have indicated similar results for compressive properties in terms of reduction and increase [52,53].…”
Section: Tensile and Compressive Propertiessupporting
confidence: 73%
“…Khanra et al [52] reported a rise in tensile yield strength, ultimate tensile strength, and a decrease in maximum strain by adding 5% HA (particle size of 1 to 5 µm) to the ZM61 matrix using a similar method. With the addition of 2.5% HA (average particle size of 600 nm), Sabet et al [53] presented an amplification in yield stress, a decrease in ultimate tensile strength, and a diminution in maximum strain. According to Figure 6(b), the compressive yield strength is augmented by 159% to 153 MPa, and the ultimate compressive strength is enhanced by 16% to 374 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…There are many reports on the fabrication of magnesium-based composites with hydroxyapatite using not only commercial purity Mg (CP-Mg) [12,13,14,15,16,17,18], but also Mg alloys such as AZ91 (Mg-9 wt% Al-1 wt% Zn) [19,20]. The usual fabrication methods involve heating, such as sintering [12,16,17] or hot extrusion [15,18,19,21]. The addition of HA within the Mg matrix, combined with mechanical processing, provides both grain refinement and a gain in strength.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is most widely used for implants, researchers recently tend to combine the titanium whit dental ceramics to improve the implants mechanical and biological properties. Hydroxyapatite (HA) is a bioceramic having excellent biocompatibility for medical applications [11]. Moreover, HA as the main component of bone and teeth has bioactive properties for new bone formation [12].…”
Section: Introductionmentioning
confidence: 99%